Cross-cultural adaptation and validation of the Chinese version of the modified Fresno test for physical therapists - Li-Yang Chen; Yi-Jing Lue; Po-Hsun Wu; Yi-Liang Kuo (BMC Medical Education)
Abstract Background The modified Fresno test was developed to assess knowledge and skills related to evidence-based practice among physical therapists and students, however no Chinese version is available. Therefore, the aim of this study was to cross-culturally adapt the English version of the modified Fresno test into Chinese and to evaluate its validity and reliability. Methods This was a cross-sectional validation study. During Phase 1 cross-cultural adaptation, forward translation, synthesis, back-translation, expert review, and prefinal test were carried out. Content validity was analyzed. During Phase 2 validation, two groups representing different levels of evidence-based practice competence completed the tests twice, two weeks apart. Known-group validity, internal consistency, and test-retest reliability were analyzed. Results Phase 1: According to the expert review, the Chinese version of the modified Fresno test demonstrated good content validity (item-level content validity index = 0.93 to 1.0; scale-level content validity index = 0.99). Phase 2: The expert group scored (115.3 ± 36.2) significantly higher than the novice group did (79.7 ± 25.8) for the entire test (p = 0.01), suggesting good known-group validity. However, the superior performance of the expert group over the novice group was not consistently found across all the questions on the test. In addition, the internal consistency was good (Cronbach’s α = 0.96) and the test-retest reliability (ICC2,1 = 0.89, 95% CI = 0.81 to 0.94) was good to excellent. Conclusions The Chinese version of the modified Fresno test is a valid and reliable tool for objectively assessing evidence-based practice knowledge and skills in Chinese-speaking physical therapists and students.